Cervical Cystic Lymphangioma in an Adult Patient. A Case Report of a Rare Entity - Tzortzis, Andrianos-Serafeim; Maniatakos, Vasileios P; Tsintzos, Simeon; Tzortzis, George (Acta medica (Hradec Kralove), 2021)
Cystic lymphangioma (CL) is a rare benign tumour that arises from the lymphatic vessels. The most common site of presentation is the posterior triangle of the neck. 90% of the lesions are diagnosed before the age of two years old and only a small number is reported in adults. In this paper, we describe the diagnostic and treatment approach of a cervical CL in an adult male.
Keywords: Child, Preschool; treatment; mužské pohlaví; neck; cystic lymphangioma; dospělí; Humans; předškolní dítě; Adult; Neck; krk; Lymphangioma, Cystic; lymfangiom cystický; lidé; Male; adult patient